Overcoming Barriers to Experience Benefits: A Qualitative Analysis of Electronic Health Records and Health Information Exchange Implementation in Local Health Departments. Issue 1 (4th September 2017) - Williams, Karmen S.; Shah, Gulzar H.; Leider, JP; Gupta, Akarti
Introduction: Electronic Health Records (EHRs) and Health Information Exchanges (HIEs) are changing surveillance and analytic operations within local health departments (LHDs) across the United States. The objective of this study was to analyze the status, benefits, barriers, and ways of overcoming challenges in the implementation of EHRs and HIEs in LHDs. Methods: This study employed a mixed methods approach, first using the 2013 National Profile of LHDs survey to ascertain the status of EHR and HIE implementation across the US, as well as to aid in selection of respondents for the second, interview-based part of project. Next, forty-nine key-informant interviews of local health department staff were conducted. Data were coded thematically and independently by two researchers. Coding was compared and re-coded using the consensus definitions. Results: Twenty-three percent of LHDs nationwide are using EHRs and 14 percent are using HIEs. The most frequently mentioned benefits for implementation were identified as care coordination, retrieval or managing information, and the ability to track outcomes of care. A few mentioned barriers included financial resources, resistance to change, and IT related issues during implementation. Discussion: Despite financial, technical capacity, and operational constraints, leaders interviewed as part of this project were optimistic about the future of EHRs in local health departments. Recent policy changes and accreditation have implications of improving processes to affect populations served. Conclusions: Overcoming the challenges in implementing EHRs can result in increased efficiencies in surveillance and higher quality patient care and tracking. However, significant opportunity cost does exist.